Glaciology and glacial geomorphology, by Wilfried Hagg, 2022 - Rachlewicz, Grzegorz (Geologos, 2023)
Review: Glaciology and glacial geomorphology, by Wilfried Hagg, 2022. Springer, Berlin/Heidelberg, 186 pages. Hardcover: price €90.94, e-book: price €71.68; ISBN 978-3-662-64713-4.